Human Capital dan Kepemimpinan Adaptif dalam Meningkatkan Kinerja Tim di Era Digital - Haidar, Arsa Bimo; Sahlah, Rifdatus; Hanifah, Delia Maghfi; Rifai, Ahmad Zedri; Falah, Rahil Septian; Utama, Rony Edward (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In today’s digital era, organizations are challenged to maintain high-performing teams amid rapid technological change and organizational transformation. Human capital and adaptive leadership are believed to be key factors in ensuring team effectiveness, yet few studies have examined their combined impact. This study aims to investigate the influence of human capital and adaptive leadership on team performance within Indonesian organizations undergoing digital transformation. Using a quantitative approach, data were collected from 102 employees working in team-based structures across private companies in Jakarta. A purposive sampling technique was used to select respondents who had worked in a team for at least six months. Data were gathered through a structured questionnaire with Likert-scale items, and analyzed using multiple linear regression with SPSS version 25. The results indicate that both human capital comprising knowledge, skills, experience, and creativity and adaptive leadership characterized by flexibility, empowerment, change management, and adaptive communication have a positive and significant influence on team performance. Furthermore, the interaction between these two variables fosters greater synergy, collaboration, and innovation within teams. These findings suggest that investments in employee competencies and the application of adaptive leadership styles are essential strategies for enhancing organizational agility and team effectiveness in dynamic environments. The study contributes to the literature on strategic human resource management and offers practical implications for leadership development in digitally evolving organizations.